A model-based head-to-head comparison of single-agent lurbinectedin in the pivotal ATLANTIS Study - Fudio, Salvador; Pérez-Ramos, Laura; Asín-Prieto, Eduardo; Zeaiter, Ali; Lubomirov, Rubin (Frontiers in Oncology, 2023)
Introduction: Lurbinectedin is a selective inhibitor of oncogenic transcription U.S. Food and Drug Administration (FDA)-approved for patients with relapsed small cell lung cancer (SCLC) as monotherapy at 3.2 mg/m² every 3 weeks (q3wk). ATLANTIS was a phase 3 study in SCLC with lurbinectedin 2.0 mg/m² plus doxorubicin 40 mg/m² q3wk vs physician’s choice, with overall survival (OS) as the primary endpoint and objective response rate (ORR) as the secondary endpoint. This work aimed to dissect the contribution of lurbinectedin and doxorubicin to antitumor effects in SCLC, and to predict the efficacy of single-agent lurbinectedin at 3.2 mg/m² in ATLANTIS to allow for a head-to-head comparison with the control arm. Methods: The dataset included exposure and efficacy data from 387 patients with relapsed SCLC (ATLANTIS, n=288; study B-005, n=99). Patients in the ATLANTIS control arm (n=289) were used for comparison. Unbound plasma lurbinectedin area under the concentration-time curve (AUCu) and total plasma doxorubicin area under the concentration-time curve (AUCDOX) were used as exposure metrics. Univariate and multivariate analyses were conducted to determine the best predictors and predictive model for OS and ORR. OS baseline hazard was best described by a log-logistic distribution, with chemotherapy-free interval (CTFI), lactate dehydrogenase, albumin, brain metastases, neutrophils/lymphocytes ratio, AUCu, and the interaction between AUCu and AUCDOX as predictors. Effect of AUCu on ORR best fitted to a sigmoid-maximal response (Emax) logistic model, where Emax was dependent on CTFI. Results: Head-to-head comparisons with predicted 3.2 mg/m² lurbinectedin resulted in a positive outcome in ATLANTIS, with hazard ratio (95% prediction intervals [95% PI]) for OS of 0.54 (0.41, 0.72), and odds ratio (95% PI) for ORR of 0.35 (0.25, 0.5). Conclusions: These results support the superiority of lurbinectedin monotherapy for relapsed SCLC over other approved therapies.